Structuring the contents of elective course material in the process of professional training of future social teachers - Клюй, Любов Вікторівна (Pedagogy of Higher and Secondary Education, 2015)
Kliuy L. V. Structuring the contents of elective course material in the process of professional training of future social teachers. The article studies the issues of didactic maintenance development for the contents of elective course in terms of socio-pedagogical training of future social teachers. Didactic maintenance as to the main directions of socio-educational activities to some extent offsets the advantage of theoretical course units against the practical one. The last one is associated with the formation of professional abilities and skills enhancing the formation of projective skills of future specialists.